MASALAH HUKUM DALAM PENGGUNAAN SPEKTRUM FREKUENSI RADIO DI INDONESIA - Asril Sitompul (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2013)
Meanwhile there are nine telecommunications operators in Indonesia have the license to use radio frequency spectrum (Mobile Network Operator – MNO) and some operators that did not have the license. With the increase of the cellular and fixed wireless operators and the increase of users of the internet provided by Internet Service Provider (―ISP‖) through wireless networks using radio frequency spectrum, then the need of Radio frequency spectrum also increased. The effort to overcome the rare radio frequency spectrum conducted by development of radio frequency spectrum technology, among others by using multiple access system. This system may be conducted by division of time, frequency, or code. Other system is by using the concept of Mobile Virtual Network Operator (―MVNO‖) by relationship between the licensed and unlicensed operators, i.e. by leasing of the spectrum. In Indonesia, there was no regulation regarding MVNO, so there was a question about whether the MVNOs include in the category of radio frequency spectrum users and whether or not the MVNO required to have license and pay the BHP for the use of frequency. Therefore it is necessary to have a change in the existing regulations to make clear the status and the existence of the unlicensed users of radio frequency spectrum as the MVNOs. Keyword: Spectrum, users, utilization, MVNO, regulation